The role of transporters on drug therapy - . Ngatidjan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
ABSTRACTPharmacodynamical studies showed that most drugs elicit their effects by acting on 3 kinds of protein molecules known as receptors, enzymes or transporters. Although their detail properties had not been explained for decades the roles of transporters in drug kinetics and dynamics has been well understood, even have been applied in the therapy. Transporters are classified into 2 major classes, the solute carriers (SLC) and ATP-binding cassette (ABC) families. SLC transporters do not possess ATP binding site property as those of ABC transporters. SLC transporters consist of 3 SLC subfamilies i.e. organic cation transporters (OCTs), organic anion transporters (OATs) and organic anion transporting polypeptides (OATPs). In contrast, ABC transporters require ATP hydrolysis to transport substrate across cell membrane. Human ABC-transporters consist of ABCA1- 13, ABCB1-11, ABCC1-12, ABCD1-4, ABCE1, ABCF1-3 and ABCG1-8 subfamily. Although the originally funtion of transporter is to transport specific physiological substrate such as nutrient, hormone, cytokines, neurotransmitters and other physiological subtances across cell membrane the specificity is not restricted to each substrate. Drugs and other xenobiotics which have structural similarity to the physiological substrates are recognized and transported by the related transporters. The competition of them on transporters therefore may lead to the occurence of drug-drug interactions (DDI) or drugphysiological substrate interaction in the drug-kinetics phase. Many transporters located in the liver, intestinal and renal epithelial cell membranes involve in the transport of endogenous substance or xenobiotics including drugs play important roles as protective barrier. Since transporters also serve as the targets of drug action it is understood that transporters play important role in the pathogenesis of diseases as well as in the drug therapy of diseases.